The Impact of the Capture Fisheries Management Program on the Welfare Level of Fishermen - Ruslan Y. Wailissa; Djufri Rays Pattilouw; Maryam Sangadji (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The study aims to assess how assistance from the capture fisheries management program has influenced the welfare of fishermen in Masohi City and Amahai sub- districts, Central Maluku Regency. Findings reveal that 20% of fishermen earned less than Rp.1 million monthly before receiving assistance, while 80% earned between Rp.1 million to Rp.5 million. Post-assistance, there was a noticeable increase in production and income, attributed to improved fishing gear, skills, and work hours. Consequently, incomes rose, with 10% earning Rp.1 million to Rp.5 million, 40% earning Rp.5 million to Rp.10 million, and 50% earning over Rp.10 million monthly. Thus, the capture fisheries management program significantly enhances fishermen's welfare.